Quality of Life in Dementia Sufferers: The Role of Diet and Exercise - Ricci, Pasquale; Massoni, Francesco; Ricci, Lidia; Onofri, Emanuela; Donato, Giuseppe; Ricci, Serafino (Current Alzheimer Research, 2018)
Background: Among the myriad of factors modulating quality of life assessments estimated in patients presenting a variety of cognitive impairments, the distinctive and critical influence of diet and exercise cannot be overestimated. Objective: The objective of this study was to review the evidence to confirm the association between these health-endowering agents and cognitive performance in People With Dementia as well as providing a correlation between Mini Mental State Examination scores and available anthropometric data. Methods: The authors tested the hypothesized correlation on a sample of subjects with instrumentally confirmed cognitive impairment using parameters as Body Mass Index and calf circumference. Results: The results confirm the hypothesis and suggesting the possible use of anthropometric data in the process of objective evaluation of the patient with cognitive impairment that could also be used for forensic medicine.
Keywords: diet